Dose to the cardio-pulmonary system and treatment-induced electrocardiogram abnormalities in locally advanced non-small cell lung cancer. (November 2019) - Hotca, Alexandra; Thor, Maria; Deasy, Joseph O.; Rimner, Andreas
Highlights: ECG abnormalities after chemo-RT in LA-NSCLC are common (35%–67%). Non-specific ECG abnormalities are associated with a high superior vena cava dose. Reducing cardiopulmonary dose is likely to lead to less radiation-induced cardiac toxicity. Abstract: Introduction: High dose radiotherapy (RT) has been associated with unexpectedly short survival times for locally advanced Non-Small Cell Lung Cancer (LA-NSCLC) patients. Here we tested the hypothesis that cardiac substructure dose is associated with electrocardiography (ECG) assessed abnormalities after RT for LA-NSCLC. Materials and methods: Pre- and post-RT ECGs were analyzed for 155 LA-NSCLC patients treated to a median of 64 Gy in 1.8–2.0 Gy fractions using intensity-modulated RT plus chemotherapy (concurrent/sequential: 64%/36%) between 2004 and 2014. ECG abnormalities were classified as new Arrhythmic, Ischemic/Pericardial, or Non-specific ( AΔECG, I/PΔECG, or NSΔECG ) events. Abnormalities were modeled as time to ECG events considering death a competing risk, and the variables considered for analysis were fractionation-corrected dose-volume metrics (α/β = 3 Gy) of ten cardio-pulmonary structures (aorta, heart, heart chambers, inferior and superior vena cava, lung, pulmonary artery) and 15 disease, patient and treatment characteristics. Each abnormality was modelled using bootstrapping and a candidate predictor was suggested by a median multiple testing-adjusted p-value ≤0.05 across the 1000 generated samples. Forward-stepwise multivariate analysis was conducted in case of more than one candidate. Results: At a median of eight months post-RT, the rate of AΔECG, I/PΔECG, and NSΔECG was 66%, 35%, and 67%. Both AΔECG and I/PΔECG were associated with worse performance status (p = 0.007, 0.03), while a higher superior vena cava minimum dose was associated with NSΔECG (p = 0.002). Conclusion: This study suggests that higher radiation doses to the cardio-pulmonary system lead to non-specific ECG abnormalities. Reducing dose to this system, along with effective tumor control, is likely to decrease radiation-induced cardiac toxicity.